Parental trust and the role of misinformation in childhood immunization decisions - Anesa Terzić; Elma Mujaković; Emir Bećirović; Minela Bećirović; Almira Ćosićkić (Medicinski glasnik, 2026)
Aim: Vaccine hesitancy challenges global public health, with parental attitudes significantly impacting childhood immunization. This study examined parental perceptions of vaccine safety, effectiveness, and decision-making factors in Bosnia and Herzegovina. Methods: A cross-sectional survey was conducted in March 2025 with 233 parents at a Primary Healthcare Center in Gračanica. A structured questionnaire based on the Parent Attitude about Childhood Vaccines (PACV) assessed sociodemographic data, vaccination experiences, information sources, and attitudes toward vaccines using a Likert scale. Results: Among 233 participants, 195 (83.7%) fully vaccinated their children, 30 (12.9%) practiced selective vaccination, and eight (3.4%) refused all vaccines. Vaccine hesitancy was significantly associated with lower education, (26.3% vs. 5.1%; p<0.001), rural residence (76.3% vs. 48.2%; p=0.002), and having three or more children (34.2% vs. 12.3%; p=0.01). Trust in healthcare professionals strongly influenced behavior, with 178 (91.3%) of parents who fully trusted doctors adhering to the immunization schedule. Concerns about autism were reported by 14 (36.8%) of hesitant parents and were significantly associated with delayed or refused vaccination (p<0.001). Conclusion: Although overall confidence was high, vaccine hesitancy persisted due to perceived risks. Strengthening healthcare communication and addressing misinformation, particularly autism concerns, may help improve vaccine uptake. Keywords: : health knowledge, immunization program, public health, vaccination coverage
Keywords: public health; vaccination coverage; health knowledge; immunization program